Seed Biochemical Analysis Based Profiling of Diverse Wheat Genetic Resource from Pakistan - Khalid, Anam; Hameed, Amjad (Frontiers in Plant Science, 2017)
Wheat is the major nutrient source worldwide. In Pakistan it has a crucial place in agriculture as well as in national economy. For seed biochemical compositional analysis, wheat germplasm (seventy seven genotypes) was collected from different agro-climatic zones of Pakistan. Significant variation (p<0.05) was observed for tested parameters among tested genotypes. Highest activity of ascorbate peroxidase (APX) was detected in Pavon (1426.67 Units/g s. wt.), catalase (CAT) in Pasban-90 (633.33 Units/g s. wt.), peroxidase (POD) in IQBAL-2000 (42579.6 Units/g s. wt.) and superoxide dismutase (SOD) in Manthar-2003 (278.93 Units/g s. wt.). Whereas maximum activity of alpha amylase was found in SH-2002 (292.70 mg/g s. wt.), esterase in Dharabi 2011 (987.80 µM/min/g s. wt.) and protease in NR-234 (11183.33 Units/g s. wt.) and highest total oxidant status (TOS) was detected in Faisalabad-2008 (390.0 µM/g s. wt.), malondialdehyde (MDA) content in Margalla-99 (679.23 uM/g s. wt.), total phenolic content (TPC) in Bhakkar-2000 (25383.33 µM/g s. wt.) and ascorbic acid (AsA) content in SH-2002 (713.0 µg/g s. wt.). Maximum total soluble sugar was found in Saleem-2000 (29.86 mg/g s. wt.), reducing sugars in Punjab-96 (12.68 mg/g s. wt.), non-reducing sugars in Saleem-2000 (27.33 mg/g s. wt.). However, highest albumins was identified in TC-4928 (352.89 mg/g s. wt.) and globulins in MEXI PAK (252.67mg/g s. wt.), salt soluble proteins in Faisalabad-2008 (162.44 mg/g s. wt.) and total soluble proteins in Punjab-96 (487.33 mg/g s. wt.) indicating good quality of wheat genotypes as well as good nutritional status. Genotypes which have been ranked high in respective parameter can be employed in breeding to enhance the nutritional quality of wheat.